DEVELOPMENT OF THE OUTPLACEMENT SYSTEM AS AN INNOATIVE METHOD OF HR TECHNOLOGIES - Liubov, Vodianka (Izdevniecība “Baltija Publishing” Valdeķu iela 62 - 156, Rīga, LV-1058, 2022)
In the conditions of an economic crisis, when production volumes decrease and, as a result, the profit of enterprises decreases, the problem of reducing the number of personnel becomes quite acute. But when dismissing his employees, the employer must remember the responsibility he assumed when hiring staff, namely the social responsibility for the employees of his enterprise. In this situation, the company can quite easily get rid of the image of an attractive employer and a reliable partner, and can, on the contrary, strengthen its authority. Therefore, the popularity of such recruiting services as outplacement, which involves legal assistance, psychological support, and the search for an adequate position, which contribute to further employment of the dismissed employee, has recently increased abroad. In Ukraine, outplacement of personnel is in the formative phase. The specific weight of enterprises that use it in the total number of enterprises in Ukraine is insignificant. Considering the above-mentioned aspects, the topic of the scientific work is relevant and timely for research. The category "outplacement of personnel" was studied due to the systematization of the views of famous scientists and their additions. Based on the analysis of literary sources, the list and content of the stages of personnel outplacement were clarified. Based on the studied foreign experience, the authors proposed a list of directions for the development of the personnel outplacement system in Ukraine. An analysis of the personnel security of Ukrainian industries was conducted and it was found that the specific weight of employees who, after being released, turned to their employer for job search issues is extremely small (5.9%). The technology for the development of the personnel outplacement system consisting of 7 stages is proposed. The list of tasks that must be solved within the framework of the outplacement program has been systematized. The social efficiency of the proposed measures was determined.
Keywords: Outplacement; recruitment; adaptation